N-(1,5-Dimethyl-3-oxo-2-phenyl-2,3dihydro-1H-pyrazol-4-yl)acetamide-naphthalene-2,3-diol (1/1) - Tan, Kong Wai; Ng, S.W.; Asiri, A.M.; Khan, S.A. (International Union of Crystallography, 2010)
In the reaction of naphthalene-2,3-diol and 4-aminoantipyrine in the presence of acetic acid, the amine function is acetylated and the resulting acetamide co-crystallizes with the diol in the title compound, C(13)H(15)N(3)O(2)center dot C(10)H(8)O(2), with 1:1 molar stoichiometry. The two components are linked by two O-H center dot center dot center dot O=C hydrogen bonds. One of the hydroxy groups interacts with the pyrazolone carbonyl O atom and the other hydroxy group interacts with the amide O atom of another component, generating a chain motif. Adjacent chains are linked into a layer motif via N-H center dot center dot center dot O interactions involving only the heterocyclic acetamide component.